Effects of Baccharis dracunculifolia Extract on Lipid Profile and Dietary Patterns in Diabetic Rats - , Bruno Moreira Soares; , Luiz Augusto da Silva; , Carlos Ricardo Maneck Malfatti; , Kelly Cristina Nogueira Soares; , Marcieli Cristina da Silva; , Marcos Roberto Brasil (Archives of Current Research International, 2025)
Aims: This study aimed to evaluate the effects of Baccharis dracunculifolia extract on glycemic regulation, lipid profile, and metabolic parameters in diabetic rats, as well as its potential as a complementary therapeutic intervention for diabetes management. Study Design: Experimental study using a controlled animal model of diabetes. Place and Duration of Study: The study was conducted at UNICENTRO between 2017 and 2018. Methodology: Fifty-six male Wistar rats (120 days old) were divided into eight groups: Tween Control (CT), Baccharis Control (CB), Diabetic Control (CDT), Diabetic Sulfonylurea (DS), and diabetic groups treated with B. dracunculifolia extract at doses of 50 mg (DB50), 100 mg (DB100), 200 mg (DB200), and 200 mg combined with sulfonylurea (DB200S). The extract was administered daily via gavage. Diabetes was induced using streptozotocin (STZ). Body weight, food intake, water consumption, and biochemical parameters (glucose, triglycerides, cholesterol, creatinine, and urea) were monitored over four weeks. Insulin levels and histological analyses of the liver, kidney, and pancreas were also evaluated. Statistical analysis was performed using ANOVA and post-hoc tests. Results: The B. dracunculifolia extract significantly reduced fasting and postprandial blood glucose levels (54.3% to 63.4% and 37.9% to 45.0%, respectively) and triglyceride levels (45.0% to 45.3%) in treated groups (p<0.05). Body weight loss in diabetic rats was attenuated in groups treated with the extract, particularly at lower doses (DB50 and DB100). Water intake was also minimized in treated groups compared to the untreated diabetic group (CDT). Additionally, the extract increased plasma insulin levels by 81.1% to 94.4% in treated groups. Histological analysis revealed reduced tissue damage in the liver, kidney, and pancreas of treated animals. No significant differences were observed in creatinine and urea levels among treated groups (p>0.05). Conclusion: The Baccharis dracunculifolia extract demonstrated notable hypoglycemic, antioxidant, and tissue-protective effects, suggesting its potential as a complementary therapy for diabetes management. These findings highlight its role in mitigating oxidative stress and improving metabolic parameters, which may help prevent diabetes-related complications. Further studies are needed to identify specific bioactive compounds and their mechanisms of action.